Crisis prevention, confidence building, and reconciliation in South Asia - Krepon, Michael, 1946-; Sevak, Amit. (New York : St. Martin's Press, 1996)
Confidence-building measures (CBMs) have been successful in the past in defusing volatile situations such as those arising from the Cold War and the ongoing problems in the Middle East. Michael Krepon and Amit Sevak have assembled a group of the best new scholars, policy-makers, and journalists currently working on CBMs and have directed their attention to another area of high conflict, South Asia. In the winter of 1986-87 and in the spring of 1990, Indian and Pakistani leaders employed CBMs to help avoid a fourth war in South Asia. But recently, these CBMs have been linked to increased friction over Kashmir. By looking at India, Pakistan, Kashmir, and China, as well as other areas, the scholars in this book convincingly argue for the viability of CBMs in effecting lasting conflict-resolution in the area.
Preface / Amit Sevak -- 1. A Time of Trouble, A Time of Need / Michael Krepon -- 2. Mending Fences / Sumit Ganguly -- 3. Avoiding Nuclear War / C. Raja Mohan and Peter R. Lavoy -- 4. Nuclear Issues: Myths and Realities / Pervez Hoodbhoy -- 5. CBMs for the Siachen Glacier, Sir Creek, and Wular Barrage / A. G. Noorani -- 6. Managing Internal Security Problems / Raju Thomas -- 7. Nonmilitary CBMs / Arun P. Elhance and Moonis Ahmar -- 8. Economic CBMs between India and Pakistan / Poonam Barua -- 9. Enemy Images: The Media and Indo-Pakistani Tensions / Navnita Chadha -- 10. Confidence Building between India and China / Kanti P. Bajpai and Bonnie L. Coe -- 11. Improving Sino-Indo Relations / Zhao Weiwen and Giri Deshingkar -- Appendix: I. Agreements between India and Pakistan -- Appendix: II. Agreements between China and India.
"A Henry L. Stimson Center book."
Includes bibliographical references and index.
Keywords: National security -- South Asia; Regionalism -- South Asia; South Asia -- Politics and government